Effects of selective logging on populations of two tropical understory herbs in an Amazonian forest - Costa, Flávia Regina Capellotto; Senna, Cristina; Nakkazono, Erika Matsuno (Biotropica, 2002)
This study examined the effects of (1) time elapsed after logging and (2) logging intensity on the total, juvenile, and adult densities, and on reproduction of Calathea altissima and Ischnosiphon arouma (Marantaceae), two monocot herb species in the understory of Central Amazonian forests. Logging was carried out experimentally at various intensities in eight plots (4 ha each) during 1987 and three plots in 1993. Five plots were left as experimental controls. In 1998, total and adult densities of the two species were greater in the plots logged 11 years before than in controls. For I. arouma, total and adult densities were also higher in the plots logged 5 years before; however, juvenile densities were less affected. The intensity of logging influenced adult density of both species but not total or juvenile densities. Densities of reproductive individuals of both species were higher in the logged areas and increased with logging intensity. The effects of time after logging and logging intensity on reproduction were indirect due to the greater number of adult plants in those areas. The observed effects were probably mediated by changes in canopy cover in logged areas. Greater light intensities in logging gaps, roads, and their margins may lead to increased reproduction, recruitment, growth, and survival, which in turn can lead to increased plant density. These results indicate that logging has long-term effects on understory plant populations.
Keywords: Density; Herb; Logging (timber); Reproduction; Tropical Forest; Amazonia; South America; Calathea; Calathea Altissima; Calathea Altissima; Ischnosiphon; Ischnosiphon Arouma; Marantaceae